Adsorption and desorption of nitrogen, phosphorus, potassium, and soil buffering capacity following application of chicken litter biochar to an acid soil - Perumal, Palanivell; Ahmed, Osumanu Haruna; Omar, Latifah; Nik Ab. Majid, Nik Muhamad (MDPI, 2020)
Adsorption and desorption of nitrogen (N), phosphorus (P), and potassium (K) soils are controlled by pH, pH buffering capacity, organic matter, and cation exchange capacity (CEC). These factors optimized to improve timely availability of N, P, and K crop use using organic amendments such as chicken litter biochar (CLB). The objective of this study was to determine the effects of CLB on N, P, K sorption and pH buffering capacity of an acid soil. Different rates of CLB were mixed with an acid soil for N, P, and K sorption and pH buffering capacity determination. The CLB increased soil pH and pH buffering capacity, but unlike P and K adsorption, the different rates of CLB significantly increased N adsorption, suggesting that this soil amendment has high affinity for N than P and K. Also, because CLB reduced N, P, and K desorption, it suggests that N in particular will be slowly released with time. The reduced N desorption but higher N adsorption further indicates that N can be temporary fixed by CLB. This work has revealed CLB is more effective controlling soil N availability for timely crop use to avoid losses.